PENGATURAN LEGITIME PORTIE TERHADAP KEWARISAN ANAK LUAR NIKAH MENURUT KUHPERDATA DAN KOMPILASI HUKUM ISLAM - Prasetya, Agung; Rahmawati, Rahmawati; Basri, Rusdaya; Rusdianto, Rusdianto; Sunuwati, Sunuwati (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
This article discusses the issue of legal inheritance for illegitimate children in inheritance law, where there are differences in the national legal system in Indonesia. According to customary law, it is permissible to give equal rights to adopted children, Islamic law allows obligatory wills, and civil law allows inheritance through gifts. The concept of legitime portie, or forced inheritance, exists to protect heirs from losing their inheritance rights. However, in its implementation there were several obstacles, for example in the case when the court confirmed a will to bequeath all assets to one of the sons, even though there were other legal heirs, based on considerations of Article 832 of the Civil Code and local customary law. Civil Code, the inheritance rights of children outside of marriage to their biological father are very dependent on legal recognition. Without this recognition, the legal inheritance relationship between the two does not exist. In contrast, in the Compilation of Islamic Law (KHI), the lineage of illegitimate children only follows the mother's line.